Utilização de um rejeito da fabricação do alumínio como carga inorgânica em espumas flexíveis de poliuretano - Sabrina Sa e Sant Anna (2008)
During the Bayer process in the aluminum industry a very fine black dust waste is discharged in the industry landfill leading to the environment contamination. This residue is rich in alumina (Al2O3) which is a compound of high commercial value. XRD patterns confirm, also, the presence of aluminium hydroxide (Al(OH)3). To find applications to this waste, flexible polyurethane foams were synthesized using this black dust as filler. Fillers are substances that are added to polymers toproduce materials with better mechanical and, also, thermal properties.In the present work, the black dust was added in the flexible polyurethane foams syntheses and the obtained products were compared with the foams produced with commercial fillers as calcium carbonate and alumina. They were also compared with the alumina recovered by the black powder, and with one mixture prepared with commercialalumina and recovered alumina. By SEM, thermal and mechanical analyses were used to characterize the flexible polyurethane foams containing the black dust. These foams showed excellent mechanicaland, also, flame retardant behaviour. DSC results of the flexible foams containing the fillers showed two glass transition (Tg) temperatures: the first at ca. -50oC due to the flexible segments of the polyurethane foams, and the other in temperatures above 0oC corresponding to the rigidsegments of the polyurethane foams. For polyurethane foams containing black dust as filler, Tg values of the rigid segment decreased, probably owing to the interaction of the filler with the polymer matrix which contribute to the diminution of the hysteresis in these foams.